Kinetic Study of Steam Gasificaiton of Palm Kernel Shell Char - Nuttapol Lerkkasemsan (My University, 2020)
Abstract In this work, we investigate the reaction mechanism of steam gasification reaction of palm kernel shell char. The experiment results which are used in this work are carried on at temperature of 1123, 1173, and 1223K. The isothermal steam gasification of palm kernel shell char is described by mathematic models including volumetric model (VM), grain model (GM), random pore model (RPM), and modified random pore model (mRPM). From results, we found that the RPM model can predict gasification of palm kernel shell char better than other models. The RPM model considers the overlapping of pore surfaces, which results in the reduction of surface area available for the reaction. The activation energy of gasification reactivity of palm kernel shell char is 152.63 kJ/mol for RPM model. The coefficient of determination of RPM model are 0.9920, 0.9995, and 0.9907 at 1123, 1173, and 1223 K respectively.
Keywords: Palm kernel; Isothermal process; Kernel (algebra); Thermochemical Biomass Conversion Processes